International Nomadic Ethnic Economy and Land Resource Conflict in Nigeria - Akpomera, Eddy (University of Nigeria Journal of Political Economy, 2022)
Nigeria, the most populous nation in Black Africa, which has been fighting terrorism from the Boko Haram sect in the north-eastern axis of the country, is currently battling a new challenge in the middle belt and southern regions: cross-border armed pastoral herdsmen forceful take-over of land resource, which has claimed thousands of lives. The political economy of international transhumance is strongly explained in the altering of the rural wealth indicators with the armed invasion of the pasture-rich communities, destruction of crops and forceful occupation of farmlands, as well as the prebendal policies of Nigeria’s political leadership with the new legal framework to arm twist southern ethnic groups to give up their land rights for nomadic pastoralism. The direct implications of the smouldering crisis are the impending food shortages in Nigeria, and the potentiality for ethnic militias as self-help mechanisms. It is recommended that cross-border arms control must be revved up for herdsmen, and the ethnic Fulani political cum economic elite in government and northern socio-cultural platforms pull the brakes on the violence in the country to avoid untoward tribal conflagration nationwide.